Analisis Ekuivalensi Leksikal Berita Fenomena Labubu di Portal Kompas.com - Yosani, Yosephine Marrietta Ardhya; Sumarlam, Sumarlam (Aksara: Jurnal Bahasa dan Sastra, 2025)
This research analyzes lexical equivalence in news articles about the Labubu phenomenon published on Kompas.com, focusing on how linguistic elements adapt to convey international cultural trends to local audiences. Lexical equivalence, as a key component of discourse cohesion, ensures the clarity and consistency of information in news texts. Using a descriptive qualitative approach, this study examines ten selected articles, identifying and classifying the types of lexical equivalence, such as repetition, synonymy, antonymy, collocation, and hyponymy. Findings indicate that affixation, including prefixes, suffixes, and combined affixations, is the most dominant strategy used in lexical adaptation, facilitating nuanced interpretations of cultural phenomena like Labubu. The affixation process creates lexical equivalence relevant to Labubu dolls, reflecting cultural, psychological, and marketing contexts in portraying scarcity, social actions, and opinions. This study provides insights into effective strategies for media adaptation of global cultural content and underscores the importance of lexical cohesion in maintaining credibility and accessibility in news discourse.Keywords: lexical equivalence, cultural adaptation, Labubu phenomenon, discourse cohesion, Kompas.com